The chain mediating role of social support and positive coping between neuroticism and depressive symptoms among graduate students - Wan, Peng; Hu, Jinsheng; Yang, Qingshuo (Frontiers in Psychiatry, 2024)
Introduction: Graduate students face unprecedented levels of neuroticism and pressure compared to their peers. Despite existing research examining the connection between neuroticism and depressive symptoms, a gap in the current understanding of the mediating mechanisms that act on this relationship, especially among this specific student population. Methods: This study investigated the potential chain-mediating roles of social support and positive coping in the relationship between neuroticism and depressive symptoms among graduate students. The participants were 1845 graduate students who provided demographic information and complete assessments including the Eysenck Personality Questionnaire (EPQ), Depression Rating Scale (BDI-II), Social Support Rating Scale (SSRS), and Coping Style Questionnaire (SCSQ). The analysis involved correlational analysis and a chain mediation model was used to investigate the associations among neuroticism, social support, positive coping mechanisms, and depressive symptoms. Results: The results show significant correlations among neuroticism, depressive symptoms, social support, and positive coping. Moreover, our findings verify that neuroticism affects depressive symptoms in graduate students through three pathways: the mediating effect of social support, the mediating effect of positive coping, and the chain-mediating effect of social support and positive coping. Discussion: Overall, the hypothesized chain model conclusively fits the data: Neuroticism directly affects depressive symptoms among graduate students and influences depressive symptoms through the mediating effects of social support and positive coping, as well as the chain mediating effects of these two variables.